Ultra-distal large-bore intracranial access using the hyperflexible Navien distal intracranial catheter for the treatment of cerebrovascular pathologies: a technical note. (1st June 2013) - Lin, Li-Mei; Colby, Geoffrey P; Huang, Judy; Tamargo, Rafael J; Coon, Alexander L
Abstract : Background: Successful neuroendovascular treatments rely on microcatheter stability from guide catheter support. We present our experience using a new large-bore 0.058 inch or 0.072 inch inner diameter (ID) hyperflexible access catheter placed deep within the intracranial circulation during the neurointervention. Methods: We retrospectively reviewed all neurointerventions performed by the senior author during an 18-month period to identify patients in whom the Navien intracranial catheter was placed in an ultra-distal position, defined as beyond the clinoidal internal carotid artery (ICA) or V3 segment of the vertebral artery. Procedural data collected included parent artery tortuosity, technique for Navien advancement, intraprocedural Navien position and periprocedural complications. Results: The Navien, either 6 F 0.072 inch ID or 5 F 0.058 inch ID, provided ultra-distal large-bore access in the following 11 intracranial interventions: anterior circulation aneurysm treatment with Pipeline embolization device (PED) (n=3); posterior circulation aneurysm single-stage stent coiling (n=5); liquid embolization of arteriovenous malformations (n=2); PED coiling of posterior circulation aneurysm (n=1). The Navien was tracked into position over a Marksman microcatheter in 10/11 cases and a Headway 27 microcatheter in one case. Intraprocedural Navien positions were as follows: supraclinoid ICA (n=2); mid M1 (n=1); V3–V4 junction (n=2) (both using 6 F Navien); distal V4 (n=3); proximal basilar (n=1); proximal-mid basilar (n=1); mid basilar (n=1). No significant catheter-related complications occurred. Conclusions: The Navien is the newest hyperflexible access catheter that is highly trackable into ultra-distal intracranial positions. It maneuvers atraumatically, providing improved distal intracranial support for a variety of complex cerebrovascular interventions and preserves necessary ID for quality intraprocedural roadmaps and angiography.